Seasonal resonance of diurnal coastal trapped waves in the southern Weddell Sea, Antarctica - S. Semper; E. Darelius (Ocean Science, 2017)
The summer enhancement of diurnal tidal currents at the shelf break in the southern Weddell Sea is studied using velocity measurements from 29 moorings during the period 1968 to 2014. Kinetic energy associated with diurnal tidal frequencies is largest at the shelf break and decreases rapidly with distance from it. The diurnal tidal energy increases from austral winter to summer by, on average, 50 %. The austral summer enhancement is observed in all deployments. The observations are compared to results from an idealised numerical solution of the properties of coastal trapped waves (CTWs) for a given bathymetry, stratification and an along-slope current. The frequency at which the dispersion curve for mode 1 CTWs displays a maximum (i.e. where the group velocity is zero and resonance is possible) is found within or near the diurnal frequency band, and it is sensitive to the stratification in the upper part of the water column and to the background current. The maximum of the dispersion curve is shifted towards higher frequencies, above the diurnal band, for weak stratification and a strong background current (i.e. austral winter-like conditions) and towards lower frequencies for strong upper-layer stratification and a weak background current (austral summer). The seasonal evolution of hydrography and currents in the region is inferred from available mooring data and conductivity–temperature–depth profiles. Near-resonance of diurnal tidal CTWs during austral summer can explain the observed seasonality in tidal currents.